Fatores influentes sobre desastres naturais relacionados às águas urbanas: um estudo em Colatina-ES - Oliveira, Dayanne Diwlyan Raasch de (2022)
The way cities are planned and governed is closely related to impacts on sustainability and resilience. These characteristics reflect, consequently, the level of vulnerability to adverse weather events. Anthropic activities have modified the planet's climate, culminating in an imbalance of natural systems and causing situations of fragility that can cause catastrophes. The main objective of this research was to identify factors that influenced the occurrences of natural disasters related to urban waters in ColatinaES, in the years 2013 and 2020, and to investigate the collaboration of urban occupation for such occurrences, within an environmental, social and urban perspective. To fulfill this purpose, a descriptive and analytical research was carried out that evaluated 71 neighborhoods located in the municipal headquarters. Through field research, with documents made available by the Civil Defense of Colatina, data about the hydrological and geological disasters that occurred in the time frame of the research were collected and georeferenced. Using the Geographic Information System, the data were integrated using a procedural logic of interpretation, classification and representation. Analyses of changes in land cover were performed from a spatio-temporal perspective and the factors influencing the occurrence of disaster were identified. As results, the research synthesized data, through descriptive mapping of the territory, of spatial modifications in time, and the list of influential factors on disasters related to urban waters. The results of the research indicated seven main influential factors on the occurrence of disasters: rainfall; income; households with trees in the surroundings; households with the presence of garbage in the surroundings; households with the presence of culverts and wolf mouths in the surroundings; the coefficient of runoff from permeable and impermeable areas; and land cover. The main contribution has been revealed aspects that influenced the occurrences of natural disasters related to urban waters, elucidating the aspects to be controlled and problems to be mitigated.